Analisis Risiko Keselamatan dan Kesehatan Kerja (K3) terhadap Pekerjaan Mekanik Menggunakan Metode Modified House of Risk (HOR) pada PT. XYZ - Septiana, Giga Dewi; Tranggono, Tranggono (Universitas Batanghari Jambi, 2025)
This study aims to conduct an analysis of Occupational Safety and Health (OCH) risks in the mechanical work of PT. XYZ and provide risk mitigation using the modified House of Risk (HOR) method. The findings of this study in HOR stage 1 are in mechanical work which includes preparing before service, finding the source of the problem, determining corrective actions, service (repair), performance test, checking around the body unit, service maintenance and after service has 34 risk events and 28 risk causes. In data processing according to the Pareto diagram principle where 80%: 20%; then the main problem that must be resolved in HOR stage 2 is 7 risk agent priorities. The results of the HOR stage 2 calculation obtained 7 prevention actions or risk mitigation that can be used as a solution to minimize the occurrence of risk causes.